Analysis of characteristics, morals and contributing factors in adolescent who have experienced school dropout: A portrait of education in PKBM Bakti Nusa Bogor - Andini, Putri Fildzah; Putri, Aisyah Puspita; Purnama, Nurjanah (Jurnal Pendidikan Karakter, 2024)
The problem of children dropping out of school still needs to be studied further because many factors contribute to this phenomenon. It is because in Indonesia, as many as 0,71 % of children drop out of elementary school, 6,49% drop out of junior high school, and 22,52% drop out of high school. This research aims to identify characteristics, moral understanding, and character development and analyze the factors that cause children to drop out. This research uses mixed methods, quantitative and qualitative, with in-depth interviews with teenagers who have dropped out of school aged 17 to 21. The research results show that economic problems, weak moral foundations, and parental style are why teenagers drop out of school. Other results showed that the moral knowledge of out-of-school teenagers was in the medium category, the moral feelings of 2 people were in the low category, and the rest were in the medium category. Regarding moral behaviour, the majority are in the low category, and the rest are in the medium category. The results of this research will be a reference for policymakers to reduce school dropout rates and increase children's character and moral values in Indonesia.